Comparing Psychometric Properties of GLFS-5 With GLFS-25 for Screening Locomotive Syndrome in Community-dwelling Iranian Older People - Nasim Sadeghi Mahall; Mohammad-Ali Hoseini; Mehdi Rahgozar; Kian Norouzi Tabrizi (Iranian Rehabilitation Journal, 2021)
Objectives: Locomotive syndrome refers to reduced mobility due to impairment of locomotive organs. Because of the importance of screening locomotive syndrome among older people, this article is focused on psychometric characteristics of Geriatric Locomotive Function Scale (GLFS)-5 and comparing it with GLFS-25 in Iranian older adults Methods: This research was conducted on 320 older Iranian people. Validity and reliability of the GLFS-5 were examined and confirmed using Content Validity Index (CVI), factor analysis, correlation coefficient with the European Quality of Life Scale-5 Dimension (EQ-5D) questionnaire, the Cronbach α value for internal consistency, and intraclass correlation and Receiver Operating Characteristic (ROC) technique to determine the cutoff score for the locomotive syndrome. Results: In phase 1 of the study, 250 Iranian older people ≥60 years were analyzed. The factor analysis showed that the GLFS-25 is a multi-dimensional scale (Activities of Daily Livings [ADLs] and Quality of Life [QoL], pain, social relationship, and psychological status), and GLFS-5 is a one-dimensional scale (the ability to perform daily activities). The Cronbach α values for GLFS-25 and GLFS-5 were 0.93 and 0.84, respectively. As for association between the GLFS-25 and GLFS-5 with EQ-5D and Visual Analogue Scale (VAS) (health self-perceived), the Pearson correlation coefficients were 0.85 and -0.72 for GLFS-25 (P=0.01) and 0.82 and -0.67 for GLFS-5 (P=0.01), respectively. The cutoff scores to identify locomotive syndrome for the GLFS-25 and GLFS-5 were 16 and 4, respectively. Discussion: Considering the good validity and reliability properties of the GLFS-5 compared to GLFS-25 and the more convenient use of this short version of the GLFS, its application is highly recommended for community-based screening of locomotive syndrome in Iranian older people.